Performance of Annealed Composite Cellulose Acetate/NaA Zeolite Membrane in Carbon dioxide/Methane Gas Separation - Asep Hadian Hadinata; Agnes Rezky Siahaan; Mohamad Ghifary; Dewi Agustina Iryani; Engela Evy Ernawati (Jurnal Kimia Valensi, 2020)
Ramie (Boehmeria nivea) is one type of plant used to produce high quality cellulose fiber. Its fiber is convertible to cellulose acetate (CA), which is commonly used as membrane’s material. Dense CA membrane is used in gas permeation process and the performance is improvable by mineral blending and annealing. This study aims to determine the characteristics of modified CA membranes and the performance in separation of CO2/CH4 gases. Membrane preparation was carried out by using phase inversion technique, while annealing was carried out at 60oC. Furthermore, NaA zeolite was added with various concentrations, which include 5, 10, 15 and 20%. Gas permeation was carried out at 4 barrer for an hour. The performance of the membrane was measured based on its permeability and selectivity. The results showed that CA membrane with 10% zeolite yielded the best performance with CO2 and CH4 permeability of 140.55 and 22.25 barrer respectively and selectivity of CO2/CH4 6.32.